Adventures in childhood intellectual property, imagination and the business of play - Bellido, Jose; Bowrey, Kathy (Cambridge intellectual property and information law, 2022)
Adventures in Childhood connects modern intellectual property law and practice with a history of consumption. Structured in a loosely chronological order, the book begins with the creation of a children's literature market, a Christmas market, and moves through character merchandising, syndicated newspaper strips, film, television, and cross-industry relations, finishing in the 1970s, by which time professional identities and legal practices had stabilized. By focusing on the rise of child-targeted commercial activities, the book is able to reflect on how and why intellectual property rights became a defining feature of 20th century culture. Chapters trace the commercial empires that grew around Alice in Wonderland, Peter Rabbit, Meccano, Felix the Cat, Mickey Mouse, Peter Pan, Eagle Magazine, Davy Crockett, Mr Men, Dr Who, The Magic Roundabout and The Wombles to show how modern intellectual property merchandising was plagued with legal and moral questions that exposed the tension between exploitation and innocence